Layered double hydroxide?indomethacin hybrid: A promising biocompatible compound for the treatment of neuroinflammatory diseases - Meneses, Carla Carolina Ferreira (Elsevier, 2021)
Indomethacin (INDO) demonstrates therapeutic efficacy in the treatment of neuroinflammatory diseases. Despite its importance as a drug, INDO causes gastrointestinal problems and adverse reactions in the central nervous system (CNS). In this study, we prepared nanoparticles of layered double hydroxide (LDH) loaded with INDO. The structure of the nanohybrid (LDH-INDO) was synthesized via a coprecipitation method, and the nanohybrid was characterized using X-ray powder diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis?differential scanning colorimetry (TGA?DSC), field-emission scanning electron microscopy (FE-SEM), and ultraviolet (UV)?vis spectroscopy. Moreover, the drug release profiles of the nanohybrid were investigated using kinetic models. INDO was incorporated within the LDH interlayer space with 50% intercalation. The release of INDO anions from LDH-INDO after 10?h was 90% at pH 4.8???0.02 and 51% at pH 7.4???0.02. The results show that the release profiles follow a pseudo-second-order model. In addition, lipopolysaccharide (LPS)-induced sickness behavior in animals and treatment with INDO and LDH-INDO suggest recovery of the variables (weight and food intake) used in this study. LDH-INDO did not alter hepatic and renal biomarkers. Moreover, LPS increased the number of Iba1+ cells (microgliosis) and caused morphological alterations in these cells in the hippocampus and somatosensory cortex. However, the LPS effect was attenuated after treatment with INDO, both free and LDH-intercalated, in both regions of the brain.